379 Initial safety, efficacy, and product attributes from the SURPASS trial with ADP-A2M4CD8, a SPEAR T-cell therapy incorporating an affinity optimized TCR targeting MAGE-A4 and a CD8α co-receptor. (9th November 2020) - Hong, David; Clarke, Jeffrey; Johanns, Tanner; Kebriaei, Partow; Heymach, John; Galal, Ahmed; Saibil, Samuel; Sacher, Adrian; Brophy, Francine; Betts, Gareth; Bath, Natalie; William, Spinner; et al.
Abstract : Background: The ongoing SURPASS trial (NCT04044859 ) evaluates safety and efficacy of next-generation ADP-A2M4CD8 SPEAR T-cells co-expressing the CD8α co-receptor with the engineered MAGE-A4 c1032 T cell receptor (TCR). Methods: First-in-human trial in HLA-A*02 positive patients (pts) with advanced cancers expressing MAGE-A4 antigen by immunohistochemistry. Eligible pts undergo apheresis, T-cells are isolated, transduced with a Lentiviral vector containing the MAGE-A4 c1032 TCR and CD8α co receptor, and expanded. Expansion, transduction level, cellular composition and function of the manufactured product (MP) are assessed in vitro. Prior to infusion, pts receive lymphodepletion with fludarabine 30 mg/m 2 /day for 4 days and cyclophosphamide 600 mg/m 2 /day for 3 days. Results: As of 16 July 2020, 5 pts (1 with MRCLS, 2 with esophagogastric junction [EGJ] cancers, 1 with ovarian cancer, and 1 with head and neck cancer) were treated with ADP-A2M4 CD8 (range 1 to 5.7 billion transduced cells). No DLTs or SAEs have been reported. To date, 1 pt with EGJ cancer had a partial response (PR per RECIST) and has had progression-free survival >6 months. One pt with head and neck cancer also had a PR. All other pts have had best overall response of stable disease.MP expanded by an average of 15.3 fold during manufacturing (range 5.9 to 25.6-fold). On average, 43% of T-cells in the MP expressed the TCR (range 23 to 63%). The fraction of CD4 + cells in the final MP varied (range 45 to 84%). Co-expression of the MAGE-A4 TCR and CD8α in CD4 + T-cells in the patient MP enabled CD4 + T-cells to kill tumor target cells directly in vitro. MAGE-A4 expression in tumor biopsies varied (H-score range 55 to 300). Transduced T-cells were detected in peripheral blood of all pts. IFN-gamma increased transiently in the serum of 1 pt who responded. Conclusions: ADP-A2M4CD8 SPEAR T-cells have shown an acceptable safety profile and pts with EGJ cancer and head and neck cancer have demonstrated evidence of antitumor activity. Translational data and early clinical results indicate that co-expression of the CD8α co-receptor on CD4 + SPEAR T-cells may increase the potency of the product by conferring additional killing activity to the helper T-cell subset. This dose escalation trial is ongoing and updated clinical and translational data will be presented. Trial Registration: NCT04044859 Ethics Approval: The trial was conducted in accordance with the principles of the Declaration of Helsinki and the International Conference on Harmonization Good Clinical Practice guidelines and was approved by local authorities. An independent ethics committee or institutional review board approved the clinical protocol at each participating center. All the patients provided written informed consent before study entry.